(untitled) (Journal of Global Accounting, 2023)
The paper examined savings as an economic diversification strategy for economic growth and development in Nigeria. The objective was to assess savings as a capital tool for the growth and development of other resources among Nigerians, particularly cooperative members. Expost facto research design was used. Secondary data were collected from co-operative societies in Nigeria. It was found that most business organizations such as sole proprietorship, partnerships and joint stock companies do not encourage thrifting like the co-operative societies. Hence, the co-operative societies operate both at the grassroots and urban sectors of Nigeria. Findings further showed that co-operative societies have the potential to influence savings behavior of their members positively. It was concluded that co-operative societies are critical partners in accelerating economic development of Nigeria. The paper recommended stronger collaboration between conventional financial institutions and co-operative societies so that more synergistic relationship could be established in order to build up the savings and economic growth of Nigerians, particularly at the grassroots and rural sector for accelerated development of Nigeria.